Examination of Motor Model Considering Magnetic Interaction of Axial-Flux SR Motor for Compact EV - Nagasawa, S.; Nakamura, K. (Transaction of the Magnetics Society of Japan Special Issues, 2025)
Switched reluctance (SR) motors are robust and inexpensive since they consist only of iron cores and windings. Therefore, SR motors can be a potential candidate for in-wheel motors of electric vehicles (EVs). In previous papers, axial-flux switched reluctance motors (AFSRMs) for a compact EV were prototyped, and novel control methods, called variable commutation period control and average torque control, were also proposed. Both control methods can expand the torque-speed range, especially in high-speed regions. However, a previous motor model of the AFSRM cannot replicate both control methods and contains errors compared to measured values due to magnetic interaction. This paper presents an improved motor model that takes magnetic interaction into account.